Azure-winged Magpies breeding in urban areas can effectively reduce the risk of brood parasitism - Jianping Liu; Yilin Lu; Fudong Zhou; Wei Liang (Avian Research, 2025)
With the ongoing acceleration of global urbanization, an increasingly larger proportion of natural habitats are being transformed and utilized by humans. Urbanization has a substantial impact on animal populations, exposing them to greater risks, but also presenting new opportunities and resources. Although the effects of urbanization and brood parasitism on the population dynamics and behavior of host birds have received considerable attention, there has been comparatively little research on how urbanization might affect the risk of brood parasitism on host birds. From April to August in 2023 and 2024, we investigated the risk of brood parasitism on Azure-winged Magpies (Cyanopica cyanus) breeding in the urban center, outskirt, and rural areas of Wuhan City, Hubei Province, China. The results revealed significant differences in the risk of brood parasitism among Azure-winged Magpies in the three regions, with the proportion of magpies parasitized by the Asian Koel (Eudynamys scolopaceus) being found to be significantly lower in the city center (0%) than that in outskirt (3.8%) and rural (11.4%) areas. Our results are consistent with the idea that cities can act as refuges that reduce the risk of brood parasitism experienced by host Azure-winged Magpies. Accordingly, breeding in cities enables Azure-winged Magpies to escape brood parasitism by the Asian Koel.